Zrównoważony rozwój na tle wybranych dylematów moralnych współczesnych społeczeństw zachodnich - Płachciak, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Difficulties of sustainable development implementation emerge out of different sources like the luck of political will, half-baked strategy for achieving expected goals, questionable legacy of financial sponsoring and others. But undoubtedly, one of the main problems of slowing down the sustainable development implementation comes out of two sources - the erosion of moral ground under the ideas of neoliberal thought and the spread of postmodern tendency of value deconstruction. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 87-98